Costs of potentially inappropriate medication use in residential aged care facilities - S. L. Harrison; L. Kouladjian O’Donnell; R. Milte; S. M. Dyer; E. S. Gnanamanickam; C. Bradley; E. Liu; S. N. Hilmer; M. Crotty (BMC Geriatrics, 2018)
Abstract Background The potential harms of some medications may outweigh their potential benefits (inappropriate medication use). Despite recommendations to avoid the use of potentially inappropriate medications (PIMs) in older adults, the prevalence of PIM use is high in different settings including residential aged care. However, it remains unclear what the costs of these medications are in this setting. The main objective of this study was to determine the costs of PIMs in older adults living in residential care. A secondary objective was to examine if there was a difference in costs of PIMs in a home-like model of residential care compared to an Australian standard model of care. Methods Participants included 541 participants from the Investigation Services Provided in the Residential Environment for Dementia (INSPIRED) Study. The INSPIRED study is a cross-sectional study of 17 residential aged care facilities in Australia. 12 month medication costs were determined for the participants and PIMs were identified using the 2015 updated Beers Criteria for older adults. Results Of all of the medications dispensed in 1 year, 15.9% were PIMs and 81.4% of the participants had been exposed to a PIM. Log-linear models showed exposure to a PIM was associated with higher total medication costs (Adjusted β = 0.307, 95% CI 0.235 to 0.379, p < 0.001). The mean proportion (±SD) of medication costs that were spent on PIMs in 1 year was 17.5% (±17.8) (AUD$410.89 ± 479.45 per participant exposed to a PIM). The largest PIM costs arose from proton-pump inhibitors (34.4%), antipsychotics (21.0%) and benzodiazepines (18.7%). The odds of incurring costs from PIMs were 52% lower for those residing in a home-like model of care compared to a standard model of care. Conclusions The use of PIMs for older adults in residential care facilities is high and these medications represent a substantial cost which has the potential to be lowered. Further research should investigate whether medication reviews in this population could lead to potential cost savings and improvement in clinical outcomes. Adopting a home-like model of residential care may be associated with reduced prevalence and costs of PIMs.